A Critical Review of Antecedents of Entrepreneurship Intention - Mwange, Austin (IJRDO - Journal of Business Management, 2018)
This is article is a critical examination of the antecedents of entrepreneurship intentions. A critical analysis of research on entrepreneurship has reveals that for one to be an entrepreneur or not, there are a variety of antecedents and the following as predominant factors; economic, demographic, environmental, psychological and social cultural factors, perception of opportunities, social cultural environment, self-efficacy, lack of competency barrier, fear of failure, perceived support, gender, family factors, perceived barriers and personality factors among others. It is these antecedents that this article examines critically